ELECTIONS FOR SALE: THE SHORTCOMINGS OF INDONESIA'S ELECTION LAW IN PREVENTING VOTE-BUYING AND ENSURING FAIR PLAY - Pujiono, Pujiono; Prasetyoningsih, Nanik (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This article examines the implications of addressing vote-buying in Indonesia for the future of democracy in the country. Vote-buying undermines democratic institutions, erodes public trust, and hampers citizen participation in the electoral process. By effectively tackling this issue, Indonesia can strengthen its democratic institutions, restore public confidence, and increase citizen engagement. Additionally, addressing vote-buying promotes fair political competition, ensures better representation, strengthens the rule of law, and enhances Indonesia's international reputation as a vibrant democracy. Overall, addressing vote-buying holds significant implications for the future of democracy in Indonesia, promoting transparency, accountability, and a vibrant democratic society.